Integrating Land Financing into Subnational Fiscal Management - Peterson, George E. (2012)
Land assets have become an important source of financing capital investments by subnational governments in developing countries. Land assets, often with billions of dollars per transaction, rival and sometimes surpass subnational borrowing or fiscal transfers for capital spending. While reducing the uncertainty surrounding future debt repayment capacity, the use of land-based revenues for financing infrastructure can entail substantial fiscal risks. Land sales often involve less transparency than borrowing. Many sales are conducted off-budget, which makes it easier to divert proceeds into operating budgets. Capital revenues from sales of land assets exert a much more volatile trend and could create an incentive to appropriate auction proceeds for financing the operating budget, particularly in times of budget shortfalls during economic downturns. Furthermore, land collateral and expected future land-value appreciation for bank loans can be linked with macroeconomic risks. It is critical to develop ex ante prudential rules comparable to those governing borrowing, to reduce fiscal risks and the contingent liabilities associated with the land-based revenues for financing infrastructure.